Analisis Kesalahan Siswa dalam Mengerjakan Soal Bilangan Berpangkat dan Bentuk Akar Berdasarkan Kriteria Kastolan - Sari, Silvia Indah; Pujiastuti, Heni (Universitas Cokroaminoto Palopo, 2022)
The focus of this research is to use Kastolan's criteria to identify errors made by students when solving math problems involving exponents and root form. Kastolan divides error criteria into three categories: conceptual, procedural, and technical. This study does include six students from MTS Negeri 1 Serang City. With test instruments, interviews, and documentation, the qualitative descriptive method was used. Data analysis techniques include the processes of data collection, data reduction, and conclusion. According to the findings, the most common errors made by students were procedural errors 27,8%, conceptual errors 13,7%, and engineering errors 8,3%. The form of conceptual errors that are done, among others, students misinterpret the problem and use the wrong formula in solving the problem. Form of procedural errors that students do not perform the appropriate and systematic completion steps, and do not solve the problem to the simplest form. While the form of technical errors that are done is the wrong students in the calculation process or in the calculation operation because of the lack of accuracy and hurry to quickly solve the problem